The roles of source expertise and message completeness in the evaluation of an online health discussion board. - Thanomwong Poorisat. (2011)
For a sensitive topic such as sexuality, many people may choose to go online to anonymously seek advice from a discussion board instead of physically visiting a doctor. Using the Heuristic-Systematic Model (HSM) as a theoretical framework, this study examines the effect of message completeness and source expertise on perceived message credibility and behavioral intentions in the context of an online health discussion board. A 2 (source expertise) x 2 (message completeness) x 2 (task importance) fully crossed between-subjects experimental study was conducted with 499 students from Uttaradit Rajabhat University in Thailand. Results show that when task importance was low, both source expertise and message completeness positively influenced perceived message credibility but not behavioral intentions. When task importance was high, message completeness became significantly more influential, while the main effect of source expertise disappeared. For both task importance conditions, the effect of message completeness was found to be more pronounced when the message was provided by a doctor. Further analyses show that when the message lacked explanation, low task importance participants were likely to use an expertise heuristic to infer message credibility. However, when the message was less complete, their perceptions of credibility were influenced more by existing knowledge. On the other hand, those with higher task importance were likely to first use an expertise heuristic to decide whether the information is worth processing and then to confirm their message judgments.